KERAGAMAN JENIS BURUNG DI KAWASAN PENGAMATAN BURUNG BIDADARI KALI BATU PUTIH, HALMAHERA BARAT, MALUKU UTARA - Ashari, Reyna; Kurniawan, Andy; Nurjannah, Siti; Yahya, Firman (MAKILA, 2024)
Kali Batu Putih ‘Standardwing Bird of Paradise Observation Area’ is located in West Halmahera, North Maluku. The forest in this area is a habitat for various species of birds, such as the Standardwing Bird of Paradise which is the icon of this location. This research was conducted with the aim of analyzing the diversity of bird species in the Kali Batu Putih ‘Standardwing Bird of Paradise Observation Area’. Bird species observations were carried out using a combination of line transect and point count methods. Bird species data collection was also carried out using the MacKinnon species list method. The forest conditions at the research location are secondary lowland forests at an altitude of 100-200 m asl. A total of 32 species of birds from 22 families were found in the research location. The Psittacidae family, the parrot group, has the largest number of species. Based on the feeding guild, insectivorous and frugivorous species are more dominant. There are three bird species categorized as near threatened on the IUCN red list and 11 species are protected by law in Indonesia. The number of endemic bird species is quite abundant, as many as 14 species or 44% of all species found. The large number of endangered, protected, and endemic bird species needs to be a concern by area managers in increasing bird conservation efforts in the Kali Batu Putih area. Conservation steps can be taken through habitat management activities, periodic monitoring, increasing biodiversity research, and developing ecotourism governance by involving communities around the forest.